Cognitive Dissonance between a Conservative and a Liberal Gender Order: How Afghan Muslim Men Overcome the Impact of Migration on their Gender Identity in Canada - Akbary, Hamid (Journal of Muslim minority affairs, 2022)
Previous research has shown that, after migration, some immigrant Muslim men experience a surge of marital conflicts—from the extent of their involvement in domestic labour, through challenges regarding the headship role of the household, to issues of divorce and child custody. In most cases, such conflicts surface against the background of a deeper conflict between the cultural gender norms in their old and new countries. There is, however, little research on how those immigrant Muslim men manage and respond to such emotional and relationship conflicts, setting the stage for stereotypical accounts based on some false Orientalist and neo-Orientalist assumptions. Based on 33 interviews with Afghan Muslim immigrant men and drawing on Festinger’s theory of cognitive dissonance as well as Berry’s typology of immigrant acculturation, this study shows the diversity of: (a) the issues over which such conflicts emerge; and (b) the responses the subjects develop vis-à-vis those conflicts. The findings provide the contours of a theoretical framework for understanding the changing and diverse nature of Muslim masculinity in future research.